Особливості прогнозування рівнів енергоспоживання України при застосуванні різних прогнозних структур економіки - Maistrenko N.Yu.; Bogoslavska O.Yu. (General Energy Institute of the National Academy of Sciences of Ukraine, 2019)
We investigated the influence of different structures of Ukraine's economy on the level of consumption of energy resources up to 2040 with regard for the potential of energy saving. The results of carried out calculations on the conservative and optimistic structures of development of country's economy point to the necessity of a significant increase in the volumes of energy resources that are required to cover the demand for them in implementation of the development programs of domestic industry, which are laid down in the Strategy of Development of the Industrial Complex of Ukraine for the period up to 2025.The development of Ukrainian economy according to the optimistic structure requires not only a significant increase in electricity consumption, but also an increase in the volume of fuel for its production, a change in the structure of generating capacities, and also the volume of investments in the construction of new and reconstruction of existing blocks of power plants on fossil and renewable fuels, transmission devices, and networks, the growth of traffic flows that cannot be achieved in near-term outlook.The program «Popyt» accelerates calculations and provides the possibility of choosing any base year as well as input of the data of gross domestic product, gross added value, and volumes of consumed fuel-and-energy resources (FER). It calculates the total volumes of FER for the future and volumes of separate types of energy resources for each type of fuel, energy and thermal energy, and FER on the whole. On the example of electric energy as the most universal energy source, with help of developed new program in the Microsoft Access environment, we performed calculations of demand for this energy resource with regard for structural and technological changes, and proposed a forecast of economic development and energy consumption of the enlarged sections of the Ukrainian economy.